Prevalence and associated factors for the development of hypothyroidism within one year of radioactive iodine therapy among patients with hyperthyroidism in HUSM. - Sayuti, Suzila Che (2013)
Hyperthyroidism is a disorder that occurs due to excess production of thyroid hormones. This condition affecting about 2% women and 0.2% men (Wood and Franklyn, 1994). In United State about 1% of the population has hyperthyroidism (Golden et al., 2009). It is a condition having multiple aetiologies, manifestations and potential therapies. A detail medical history will provide the clinical sufficient to suggest the diagnosis of hyperthyroidism. The proper treatment of hyperthyroidism depends on recognition of symptoms and signs of the disease and the aetiologies of the disorder. The most common cause of hyperthyroidism worldwide and including Malaysia, is Grave’s disease(GD). Other causes include toxic multinodular goiter(TMNG), toxic adenoma and thyroiditis. The treatment of hyperthyroidism is directed toward lowering the serum concentrations of thyroid hormones to reestablish a eumetabolic state. The diagnostic workup begins with a thyroid stimulating hormone level test. There are three available modalities of treatment all of which are effective. These include antithyroid drugs, radioactive iodine therapy and thyroid surgery. In United State, RAI is treatment of choice in patients without contraindication (Reid and Wheeler, 2005). The main complication of RAI therapy is hypothyroidism. Many reports have documented that incidence of hypothyroidism is significant during the first year or two after treatment with RAI. The were sufficient evidence that risk factors such as dose of RAI, presence of autoantibodies, aetiology of hyperthyroidism, administration of antithyroid drug and goiter size, individually influence the outcome following RAI therapy. The aetiology of hyperthyroidism is an important factor influencing the outcome after RAI therapy. A higher incidence of hypothyroidism has been reported in patients with Grave’s disease compared with toxic multinodular goiter and solitary thyroid nodule. A higher rate of single dose treatment failure was observed in patients with multinodular goiter compared with Grave’s disease and solitary toxic nodules (Bertelsen et al., 1992). Toxic multinodular goiter is relative resistant to RAI therapy requiring doses higher than widely appreciated and unlike Grave’s disease hypothyroidism is relatively uncommon (Tzavara et aL, 2002) Although hypothyroidism is predictable sequale of radioactive iodine therapy, the time of its occurrence can be many years later. An early detection of hypothyroidism will allow prompt treatment. The rate of hypothyroidism at 12 months after RAI therapy at doses 10-20 mCi was 50% (Ekpebegh et al., 2008). In a study done by Ahmad et al (2002), the prevalence of hypothyroidism post RAI therapy was 55.8% at 1 year. Grave’s disease, presence of autoantibodies, no antithyroid treatment prior therapy, nonpalpable thyroid gland and high dose of RAI 550 MBq (15mCi) were identified as significant independent risk factors for the development of hypothyroidism post RAI therapy.